Pleuroparenchymal fibroelastosis in association with carcinomas - Baroke, Eva; Heußel, Claus Peter; Warth, Arne; Eichinger, Monika; Oltmanns, Ute; Palmowski, Karin; Herth, Felix; Kreuter, Michael (Respirology, 2016)
PPFE is a rare disease characterized by upper lobe pleural fibrosis and parenchymal fibroelastosis. Its aetiology is considered idiopathic, although possible causative factors have been described. An association of PPFE with solid tumours is unknown and has not been considered previously. We identified six patients with PPFE, four of them with a coexisting malignancy. The case series suggests that PPFE might be an implication of varying factors rather than being an exclusively idiopathic condition.